Feminist strategies in international governance - Caglar, Gulay; Prugl, Elisabeth; Zwingel, Susanne 1968- (Global institutions series, 2013)
The book combines a critical reflection on the current state of feminist politics with an introduction to urgent issues on the contemporary international agenda. In addition, the book draws on innovative conceptualizations from constructivism in international relations, legal anthropology and discourse theory to provide new framings of current feminist struggles.